Sonographic Comparison of Morphologic Characteristics Between Pilonidal Cysts and Hidradenitis Suppurativa. (26th June 2017) - Wortsman, Ximena; Castro, Ariel; Morales, Claudia; Franco, Carmen; Figueroa, Andres
Abstract : Objectives: To compare the sonographic characteristics of pilonidal cysts and hidradenitis suppurativa. Methods: A retrospective study of sonographic examinations was performed on 2 groups: 1 with pilonidal cysts and the other with hidradenitis suppurativa. The sonographic characteristics of the pilonidal cyst and hidradenitis suppurativa groups were analyzed, compared, and correlated, including an analysis of the histologic findings. For the pilonidal cyst group, the distribution, morphologic characteristics, location, shape, diameter, axis, vascularity, and scarring were also described. Statistical analyses included Spearman, Wilcoxon, Kruskall‐Wallis, χ 2, and Fisher tests. Results: The sonographic examinations of 84 patients were reviewed: 43 with pilonidal cysts and 41 with hidradenitis suppurativa. The comparison of the morphologic characteristics of the key lesions between the pilonidal cyst and hidradenitis suppurativa groups showed no statistically significant differences ( P < .05). Both groups had similar dermal and hypodermal saclike and bandlike structures that communicated with the widened base of the hair follicles. Retained fragments of hair tracts within the lesions were sonographically detected in both pilonidal cysts (100%) and hidradenitis suppurativa (83%) and also found on histologic specimens; however, the density of hair tracts per structure was higher in pilonidal cysts. Sonographic signs of scarring were absent in 63% of pilonidal cysts. Only 2% of pilonidal cysts showed communicating bandlike structures. Conclusions: Key lesions of pilonidal cysts and hidradenitis suppurativa have similar sonographic morphologic characteristics, which suggests that a pilonidal cyst may be a variant or localized form of hidradenitis suppurativa. The retained fragments of hair tracts frequently detected in both entities may be caused by ectopic production of hair and not by embedding. Common therapeutic strategies and research can be designed for both entities.